The Carnivalization and Marginality in Los Dorados (1999) written by Sergio Muñoz Chacón - Montero Rodríguez, Shirley (2018)
The present article is an analysis of the Costa Rican narrative  of the end of the 20th century and the beginning of the 21st century through the text Los Dorados (1999) written by Sergio Muñoz Chacón. At first, the discursive construction of literary postmodernity is studied, starting from the process of "carnivalization", according to the theoretical proposal of Mikhail Bakhtin. Second, the marginality is examined as a discourse that allows the symbolic construction of the text, based on the notions of investment and crisis. Finally, the critical questioning of the discourse on Costa Rican national identity is observed in this this finisecular narrative text.